A dynamic network model for the action of low salinity on two-phase flow. (March 2020) - Wilmott, Z.M.; Breward, C.J.W.; Chapman, S.J.
Highlights: Multicomponent ion exchange is incorporated into a dynamic network model. The model exhibits the low salinity effect in both secondary and tertiary mode. Approximately 5% additional oil is recovered by low salinity injection. Recovery increase due to low salinity scales linearly with the viscosity ratio. Abstract: Experimental evidence shows that decreasing the salinity of the injection water during the oil recovery process can lead to an increase in the amount of oil recovered. While the ion-exchange reactions which cause this effect are well understood in an industrial setting, there is a limited understanding of how to quantitatively describe the macroscale low salinity effect in terms of the microscale mechanisms. In this paper, we derive a dynamic network model for the salinity-dependent two-phase flow of oil and water through a porous medium in which the salinity of the water affects the thickness of the thin water layer separating the oil phase from the solid surface through the multicomponent ionic exchange mechanism, which results in a salinity-dependent slip condition on the effective oil-solid interface. We solve the network model numerically for a drainage stage followed by waterflood stage on a 30 × 30 network with random pore and throat radii distributions, and present results averaged over multiple simulations. Low-salinity waterflooding is compared with high-salinity waterflooding in both secondary and tertiary mode. Our model is able to reproduce the low salinity effect observed experimentally, in which the amount of oil produced increases as the salinity of the injection brine decreases.